Digital transformation in global higher education: A review of literature and implications for Vietnamese universities - Pham, Thi To Loan (Tạp chí Khoa học Đại học Đồng Tháp, 2023)
Digital transformation in higher education has become a common trend in the pursuit of a sustainable education system in the future. This trend fosters higher education institutions to implement teaching, learning and research activities in an innovative and creative way. Globally, universities are making efforts to boost digital transformation application as a way to maintain their competitive advantages. This literature review aims to discuss digital transformation in global higher education, elaborate types of digital transformation, digital transformation frameworks for universities and put forth implications for Vietnamese higher education. It is hoped that this paper will provide insights into digital transformation in higher education in the world so that educators, policy makers and university leaders can collaborate and take proper actions to enhance the effectiveness of digital transformation application.